Rethinking Sanctuary: The Origins of Non-Cooperation Policies in Social Welfare Agencies. Issue 1 (14th February 2023) - Fox, Cybelle
Abstract : Too often, scholarship on immigration conflates sanctuary ordinances with the non-cooperation policies, often embedded in these ordinances, which limit cooperation between local officials and federal immigration authorities. In this article, I disentangle the two by tracing the rise of non-cooperation policies in health and welfare agencies since the New Deal. Doing so challenges assumptions about the origins, targets, consequences, and significance of early sanctuary policies. It reveals that non-cooperation was federal policy between 1935 and the early 1970s, when local, state, and federal officials began to experiment with cooperation. When the consequences of such practices became clear, welfare and health officials were forced to reaffirm non-cooperation just before the sanctuary movement burst onto the scene. This research clarifies why scholars see early sanctuary ordinances as largely symbolic: because many local, state, and federal officials had largely abandoned cooperation in practice. It also challenges the widespread assumption that non-cooperation fundamentally represents local resistance to federal power. Instead, I demonstrate the key role played by the federal government in the rise of non-cooperation in health and welfare agencies. Lastly, this research reaffirms the significance of the fragmented nature of federal institutions for promoting immigrant rights.